2019
DOI: 10.1128/jvi.01700-18
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a Subacute Sclerosing Panencephalitis Genotype B3 Virus from the 2009-2010 South African Measles Epidemic Shows That Hyperfusogenic F Proteins Contribute to Measles Virus Infection in the Brain

Abstract: During a measles virus (MeV) epidemic in 2009 in South Africa, measles inclusion body encephalitis (MIBE) was identified in several HIV-infected patients. Years later, children are presenting with subacute sclerosing panencephalitis (SSPE). To investigate the features of established MeV neuronal infections, viral sequences were analyzed from brain tissue samples of a single SSPE case and compared with MIBE sequences previously obtained from patients infected during the same epidemic. Both the SSPE and the MIBE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 40 publications
1
43
0
1
Order By: Relevance
“…The hyperfusogenic properties facilitate the virus for cell‐cell fusion with SLAM and nectin‐4 deficient neuronal cells. H protein and its interaction with a specific neuronal receptor is also important for viral spread between neurons . F protein–mediated transmission of the virus across synapse to another neuronal cell can potentially be inhibited by a fusion inhibitor peptide and antibodies against the measles virus H protein.…”
Section: Transneuronal Spread In the Brainmentioning
confidence: 99%
“…The hyperfusogenic properties facilitate the virus for cell‐cell fusion with SLAM and nectin‐4 deficient neuronal cells. H protein and its interaction with a specific neuronal receptor is also important for viral spread between neurons . F protein–mediated transmission of the virus across synapse to another neuronal cell can potentially be inhibited by a fusion inhibitor peptide and antibodies against the measles virus H protein.…”
Section: Transneuronal Spread In the Brainmentioning
confidence: 99%
“…To observe the next step in viral entry, the temperature was warmed to allow activation of F to occur, while progress towards fusion was blocked using VIKI-PEG 4 -chol, a peptide that corresponds to the C-terminal heptad repeat (HRC) region of F protein [85,[104][105][106][107][108][109] and binds to the extended intermediate states of F [41,110] (Fig 4, S4 and S5 Figs, S3 Movie). To capture the transient intermediate fusion state just after HN activates F, receptor-bearing target erythrocyte fragment membranes were exposed to virus on grids at 37˚C, in the presence of the fusion inhibitory peptide VIKI-PEG 4 -chol [33].…”
Section: Capture Of the Transient Intermediate State Of F Extended Amentioning
confidence: 99%
“…Since these hyperfusogenic F proteins still require the H protein to induce membrane fusion and anti-H protein monoclonal antibodies inhibit membrane fusion mediated by hyperfusogenic F proteins, there must be a specific neuron receptor(s) interacting with the H protein (14). Furthermore, these hyperfusogenic F proteins are structurally unstable and more readily triggered for the conformational changes (13,(21)(22)(23)25).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that specific substitutions in the ectodomain of the F protein are critical for neuropathogenicity of MeV, conferring on the virus the ability to spread in primary human neurons in vitro as well as in the brains of experimentally infected mice and hamsters (6,(12)(13)(14)(21)(22)(23)(24)(25)(26). These substitutions were shown to destabilize the prefusion form of the F protein, rendering it hyperfusogenic.…”
mentioning
confidence: 99%